Protection of children through foster care under Islamic law: sustaining foster children protection through breastfeeding - Mohd, Azizah (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Islamic law has one of its objectives, the protection of people in general and children in particular. Foster care is one of the ways in which this objective is realized. The paper argues that Islamic law recognizes foster care as one of the means of protection to children who are in need of care and protection. The paper therefore distinguishes between foster care in Islamic law and adoption and the position of I slam on the two seeming but contradictory concepts. It also discusses the relationship between foster care and suckling of a child not biologically related and submits that foster care in relation with breastfeeding of the foster children would promote and offer an adequate protection to the children who are in need of it.